PEMODELAN LANSKAP REALISTIK DAN INTERAKTIF DENGAN METODE PERLIN NOISE PADA LINGKUNGAN VIRTUAL 3D - riyadi, sigit; Al Farizi, Salman (SPIRIT, 2025)
Development and performance evaluation of a 3D terrain generator application that heavily utilizes the Perlin Noise algorithm on the Android platform. The application was designed to generate virtual landscapes of varying complexity and was then tested on four Android devices with different hardware specifications. Testing was conducted to evaluate application performance in terms of frame rate (FPS), rendering time, memory usage, and the number of spawned objects. The test results showed that device specifications, particularly RAM capacity, significantly impacted application performance. Devices with more RAM demonstrated better performance, with higher frame rates and faster rendering times, while devices with lower specifications experienced decreased performance. Although the application's memory usage proved efficient and consistent across all tested devices, these results highlight the need for further optimization to ensure the application runs smoothly on lower-spec devices. This study demonstrates potential optimizations in developing terrain generator applications on the Android platform, as well as suggested improvements to enhance performance and user experience across devices.